Competences level and its perceived importance: a case study in Malaysia companies / Sharifah Fadzlon Abdul Hamid, Zairul Nurshazana Zainuddin and Suzana Sulaiman. - Abdul Hamid, Sharifah Fadzlon; Zainuddin, Zairul Nurshazana; Sulaiman, Suzana (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2016)
The Chartered Global Management Accountant (CGMA) has introduced a framework as a guideline to determine the required competences among management accountants at all levels. The effort is to assist human resource in recruiting the right candidates for positions offered in their organizations with the expectation of reducing the employability gap. Management accounting has transformed over the decades forcing management accountants to acquire various competences for them to be relevant. The roles and the tasks of management accountants have changed in many organizations to fit the expectations of their stakeholders. Certain levels of skills and competences among management accountants are therefore considered necessary in ensuring that organizations are able to meet their targets and objectives. Cost-conscious organizations expect their staff to be multi-tasked in ensuring timely and effective decisions can be made. This study shows that managers from four Malaysian companies agree that management accountants should possess the competences and skills underlined by the CGMA framework. However, they perceived the four competences (technical, business acumen, people skill, leadership) as equally important at both the operational and managerial level (which differs from the framework set by CGMA).